The relationship between triglyceride to high-density lipoprotein cholesterol ratio and cardiovascular high risk: a cross-sectional investigation - Li, Pengcheng; Cai, Jirui; Yuan, Shuaifang; Li, Yapeng; Shi, Huiting; Liang, Cui; He, Bing; Xie, Qiaotao; Lei, Baocang; Bai, Jing; Wang, Nan; Liu, Dongliang; et al. (Frontiers in Endocrinology, 2025)
AimsThe triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio reflects the balance between atherogenic and anti-atherogenic lipid fractions. The study aims to investigate the utility of the TG/HDL-C ratio in identifying high-risk groups for cardiovascular disease (CVD) within the general population.MethodsThe current study was a branch of the ChinaHEART cohort in middle China that involved a total of 6,593 community-dwelling adults. We examine the association between TG/HDL-C and CVD high-risk in a cross-sectional investigation.ResultsResults from restricted cubic spline and ROC analyses revealed a significant relationship between higher TG/HDL-C levels and increased odds of CVD high-risk, with the ratio exhibiting good discriminatory power (AUC = 0.820 in the fully adjusted model). Logistic regression further supported this association, indicating a 1.21-fold rise in the odds of high risk for each unit increase in TG/HDL-C.ConclusionsThe TG/HDL ratio shows promise for CVD risk assessment. Incorporating the TG/HDL ratio into risk assessment models may provide supplementary information to healthcare professionals for risk stratification.